Personal Informatics, Self-Insight, and Behavior Change: A Critical Review of Current Literature. (2nd November 2017) - Kersten-van Dijk, Elisabeth T.; Westerink, Joyce H.D.M.; Beute, Femke; IJsselsteijn, Wijnand A.
Abstract : Personal informatics (PI) systems allow users to collect and review personally relevant information. The purpose commonly envisioned for these systems is that they provide users with actionable, data-driven self-insight to help them change their behavioral patterns for the better. Here, we review relevant theory as well as empirical evidence for this self-improvement hypothesis. From a corpus of 6, 568, only 24 studies met the selection criteria of being a peer-reviewed empirical study reporting on actionable, data-driven insights from PI data, using a "clean" PI system with no other intervention techniques (e.g., additional coaching) on a nonclinical population. First results are promising—many of the selected articles report users gaining actionable insights—but we do note a number of methodological issues that make these results difficult to interpret. We conclude that more work is needed to investigate the self-improvement hypothesis and provide a set of recommendations for future work.